2011
DOI: 10.1080/14445921.2011.11104342
|View full text |Cite
|
Sign up to set email alerts
|

The Impacts of Commercial Lease Structures on Landlord and Tenant Leasing Behaviours and Experiences

Abstract: The commercial property market in New Zealand is characterized by two standard but distinct lease environments. In Auckland, the commercial core of the economy, net leases dominate, whereas in Wellington, the political capital, gross leases are dominant. These different lease environments have the potential to strongly influence the nature of landlord and tenant relationships in these markets. Using in-depth interviews with key industry personnel, this study examines the perceptions, behaviours, experiences an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 22 publications
1
4
0
Order By: Relevance
“…Occupier satisfaction was found to be highest in the USA (4.09/5) and lowest in South Africa (3.43/5). The study found that tenants occupying the largest amount of space had higher overall satisfaction, supporting the findings of the UK OSI studies (KingsleyLipseyMorgan and IPD Occupiers, 2008), and other research that has demonstrated that larger organisations have higher levels of satisfaction, apparently as a result of obtaining better terms because of their clout (Crosby et al , 2006; Halvitigala et al , 2011). Interestingly, this view is not supported by the recent study into the satisfaction of office occupiers in the UK (British Council for Offices and RealService Ltd, 2015) in which respondents felt that “it is not the case that the big occupiers are getting the best service and smaller occupiers are losing out” (p. 16).…”
Section: Review Of Previous Researchsupporting
confidence: 81%
“…Occupier satisfaction was found to be highest in the USA (4.09/5) and lowest in South Africa (3.43/5). The study found that tenants occupying the largest amount of space had higher overall satisfaction, supporting the findings of the UK OSI studies (KingsleyLipseyMorgan and IPD Occupiers, 2008), and other research that has demonstrated that larger organisations have higher levels of satisfaction, apparently as a result of obtaining better terms because of their clout (Crosby et al , 2006; Halvitigala et al , 2011). Interestingly, this view is not supported by the recent study into the satisfaction of office occupiers in the UK (British Council for Offices and RealService Ltd, 2015) in which respondents felt that “it is not the case that the big occupiers are getting the best service and smaller occupiers are losing out” (p. 16).…”
Section: Review Of Previous Researchsupporting
confidence: 81%
“…One tenant requirement that has put significant pressure on property managers to improve their performance is the demand for flexibility. Long-term leases have historically been the norm in developed real estate markets because they provide landlords with greater cash flow stability across economic cycles than short term leases (Bannister, 2008; Crosby et al , 2006; Edington, 1997; Halvitigala et al , 2011). However, this is starting to change.…”
Section: The Growing Importance Of Customer-focused Property Managementmentioning
confidence: 99%
“…An activity that does require a personal touch is making sure tenants understand and appreciate what they are getting for their money. This is important in all situations, but perhaps never more so than when landlords assess service charges on top of rent (Halvitigala et al , 2011). Poorly understood service charges can lead to conflicts with tenants that stand in the way of customer-focused property management.…”
Section: Best Practices In Customer-focused Property Managementmentioning
confidence: 99%
“…The landlord – tenant relationship is typically perceived as being confrontational (Crosby et al , 2003; Halvitigala et al , 2011). The role of the landlord’s leasing agents and property managers has been to “maximise rents, with rapid recourse to legal process to resolve disputes between landlord and tenant” (Sanderson, 2015).…”
Section: Literature Reviewmentioning
confidence: 99%